Kinetics and Mechanism of meso-Tetraphenylporphyriniron(III) Chloride Catalyzed Oxidation of Indole by Peroxomonosulphate - Kungumathilagam, D.; Karunakaran, K. (Asian Journal of Chemistry, 2013)
Mechanistic study on meso-tetraphenylporphyriniron(III) chloride (TPP) catalyzed oxidation of indole by peroxomonosulphate in aqueous acetonitrile medium have been carried out. The reaction follows a fractional order (0.57) with respect to substrate and first order with respect to oxidant. The order with respect to catalyst was found to be one. Increase in percentage of acetonitrile decreased the rate of the reaction. The added H+ did not affect the reaction rate. The reaction fails to initiate polymerization and free radical mechanism is ruled out. Activation and thermodynamic parameters have been computed. Nucleophilic attack of the ethylenic bond on the persulphate oxygen in presence of meso-tetraphenylporphyriniron(III) chloride is envisaged to explain the reactivity. A suitable kinetic scheme based on the observations was proposed. Significant catalytic activity is observed for the reaction system in the presence of meso-tetraphenylporphyriniron(III) chloride.